PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR PADA MATERI LISTRIK DINAMIS - Hia, Faldo Renata; Sihombing, Eidi (Universitas Negeri Medan, 2016)
The aim of research is to know the effect of problem based learning model on studentâs learning in the subject of dynamic electricity in X SMA Negeri 15 Medan A.Y. 2015/2016. The type of experiment is quasi-experimental using two group pretest-posttest design. The population is all the student X grade of SMA Negeri 15 Medan consists of 10 classes. The samples of the experiment were taken from 2 classes that determined with cluster random sampling technique, with the class X-7 as the experiment class and class X-1 as control class. The instruments that used is learning test result in essay with 10 questions that have been validated and the studentâs learning observation activities sheet. To test the hypothesis used regression test with y = -0,162x + 69,32 and RÂ² = 0,043 with the result that R = 0,207 with theÂ percentage increase 20,7%, after the prerequisite test is done, that is normality test and homogeneity test. The experiment results showed: (1) the problem based learning model can improve studentâs learning activities and (2) there is the effect of problem based learning model on studentsâ learning outcomes in the subject matter dynamic electricity in class X SMA Negeri 15 Medan 2015/2016.